Influencing factors on the vibrational and rotational temperatures in the spark discharge channel. (1st May 2021) - Huang, Shuai; Li, Tie; Zhang, Zhifei; Wang, Linyan; Yu, Xiao; Zheng, Ming; Yang, Rundai; Zhao, Xinwu
Abstract: Plasmas are widely used in engines as ignition sources and combustion assistances. Quantitative and qualitative analyses of the effects of plasmas on ignition are of great importance for improving engine performance, but with challenges. In this study, the vibrational and rotational temperatures are calculated based on the N2 second positive molecular emission spectra, with different discharge powers, ambient pressures, gas compositions, and spark plug gap sizes. The spatial distribution of the rotational temperature is also investigated. With an increased discharge power, the vibrational and rotational temperatures increase, while the difference between the vibrational and rotational temperatures decreases. As the pressure ambient increases from 0.3 to 5.0 bar, the vibrational temperature decreases initially and increases subsequently. The rotational temperature increases with the increased pressure, while the temperature difference decreases. The gas composition and gap size greatly affect the vibrational and rotational temperatures. The rotational temperature increases with the enlarged gap size, and the difference between the vibrational and rotational temperatures decreases. For the spatial distribution of the rotational temperature in the spark gap, the highest rotational temperature occurs near the center of the spark gap. Meanwhile, the rotational temperature near the central electrode is higher than that near the ground electrode. Highlights: The plasma temperatures increase with the increased discharge power. The enhanced pressure accelerates the plasma into the thermal equilbrium state. The gas compositions greatly affect the plasma temperatures. The rotational temperature increases with the increased gap size. The highest rotational temperature occurs near the center of the gap.